Changes in Olfactory Sensitivity and Odor Preference During the Sexual Cycle - Yoshinaru, Mai; Emori, Yoko; Kawaguchi, Takayasu (Journal of Japan Society of Nursing Research, 2019)
The purpose of this study was to clarify the changes in olfactory sensitivity and odor preferences during the sexual cycle. The subjects were 36 mature females in their twenties with normal olfactory functions and a stable menstrual cycle. Olfactory tests were conducted at two points in the luteal and follicular phases in the mature women using the T&T olfactometer, the only standardized olfactory measurement device in Japan. As a result, only isovaleric acid (C5H10O2) showed a lower detection threshold (p<.05) because a higher olfactory sensitivity in the luteal phase than in the follicular phase. Isovaleric acid has a putrid or human body odor. In the luteal phase, those who responded that they liked the standard odor A ( β-phenyl ethyl alcohol: C8H10O) tended to have a higher cognitive threshold than those stating that they disliked it (p<.05). There was no change in olfactory sensitivity and other odors during the sexual cycle.